Neutrosophic Battery: An Introduction to High-Performance Battery Configuration (Bulletin of Pure and Applied Sciences – Physics, 2022)
Nowadays, great effort has been focused on various kinds of batteries commonly  referred to as electric energy storage systems (EESS), such as lithium-related  batteries, sodium-related batteries, zinc-related batteries, aluminum-related batteries  and so on. Some cathodes can be used for these batteries, such as sulfur, oxygen,  layered compounds. In the present article, let us consider the basic battery con figuration, i.e. they are mostly composed of cathode and anode metals. Such a classic  system can be considered as ”two elements” model. Based on Neutrosophic Logic as  developed by one of us (FS), we consider in this paper that actually we can extend it  further to become a Neutrosophic battery system, consists of three-elements (or may  be more), i.e. cathode-anode-catalyst system. The catalytic electrolyte method is  found to be significant to achieve high-performance battery.